Tumor growth is suppressed in mice expressing a truncated XRCC1 protein - Pettan-Brewer, Christina (e-Century Publishing Corporation, 2012)
Tumor progression depends on the support of cells in the microenvironment, and is driven in part by the generation of reactive oxygen species (ROS). ROS can damage DNA, and the repair of damaged DNA is a well-known process involved in tumor initiation and promotion, but the role of DNA repair in tumor progression is not fully understood. In this regard the X-ray cross complementing 1 (XRCC1) protein is known to orchestrate the assembly of repair complexes at sites of DNA single strand breaks either directly or indirectly through repair of damaged bases, largely as the result of ROS-induced damage. XRCC1 polymorphisms have been shown to be associated with increased cancer. It was therefore of interest to investigate the effect of XRCC1 gene mutations on cancer progression. In an attempt to make XRCC1 point mutant mice, we generated a truncated protein (XRCC1tp) by the insertion of a neomycin cassette in intron12 of the XRCC1 gene. This unique finding allowed us to investigate cellular and tumor progression phenotypes in mice associated with expression and function of an altered XRCC1 protein on one allele. XRCC1tp cells showed increased toxicity to MMS, enhanced MMS-induced depletion of NADH suggesting increased PARP activity, and normal functional repair of MMS-induced DNA damage. Six months following treatment with the alkylating carcinogen azoxymethane (AOM) at 10 mg/kg once a week for 6 weeks, XRCC1tp mice had a decrease in average colon tumor volume of 14±3 mm(3) compared to 34±4 mm(3) in WT littermates (p ≤ 0.03, N= 20/genotype). XRCC1tp mice had a 72 per cent decrease in B16 melanoma tumor burden compared to wt littermates. Average tumor volume in transgenic PyMT metastatic breast cancer mice expressing XRCC1tp was 359 cubic mm in PyMT mice expressing XRCC1tp compared to 730 cubic mm in PyMT mice expressing XRCC1wt (p ≤ 0.001, N= 20/genotype). These data suggest that the presence of an XRCC1 truncated protein alters XRCC1 function independent of DNA repair, and is associated with anti-tumor activity.